Design of DBA algorithm in EPON upstream channel in support of SLA - WANG Dong; QIU Kun; WANG Li-cun (Tongxin xuebao)
Based on the SLA （service level agreement） in access network, the inherent deficiencies of two classical DBA algorithms: IPACT and Cyclic DBA in EPON to support multi-user types were analyzed. Two new Ethernet control frames: grant frame and request frame were introduced and a novel DBA algorithm supporting multi-user types SLA in EPON system: HPFCT （hierarchy polling with fixed cycle time） was proposed. The theoretical analysis and simulation results show that this algorithm meets the standard of various user types: satisfied delay and delay jitter performance of high priority services, and stable buffer size of all sorts of services. At the same time, HPFCT solves the downstream bandwidth waste problem of conventional algorithms.